Determinants of Failure to Grow on Toddlers (Stunting) - Aprina Aprina; Erwandi Erwandi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The incidence of stunting in infants illustrates the problems felt in each country in 2017 of 22.2% (World Health Organization, 2018), the prevalence of stunting infants in Indonesia in 2017, the prevalence of stunting has differed to 29.6% (Ministry of Health RI, 2018), Lampung is located in the 10th place as a province with a very large type of stunting (40%) and Central Lampung district. Lampung is currently getting information on stunting babies which were found to be 40 babies (16.2%). The purpose of this study was to identify the Determinants of Developmental Failure (Edit) in Children in Tanjung Rejo Village, Central Lampung Regency in 2021. This type of quantitative research with a Case-control approach, The size of the illustration can be determined by the Lemeshow formula so that the sample size is 40 toddlers for the case group and 40 toddlers for the control group. The sampling technique is simple random sampling. The bivariate analysis uses the Chi-Square test. and Multivariate Analysis with Logistic Regression Test. The results of the research obtained a p-value of 0.000 which means that there is an effect of birth length with Stunting Events. p-value 0.210 with OR OR 444 (95% CI0, 122-1.617) if birth weight is present with Stunting Events, p-value 0, 000. There is an effect of exclusive breastfeeding with Stunting Events. p-value 0.000, there is an effect of Breastfeeding up to 2 years with Stunting Events, p-value 0.001, there is an effect of Immunization Status with Stunting Events, p-value 0.001, there is an influence between birth spacing and Stunting Events, p-value 0.001, there is an effect of the number of children with stunting events, p-value 0.000, there is an influence of economic status with stunting events and the aspect with a very large risk of stunting is economic (95% CI 0.852-70. 346), it should be attention in terms of economic access and meeting the needs that are moderate or less for families with babies which will affect the quality of food consumption for family members. Abstrak: Kejadian stunting pada balita merupakan masalah yang dialami hampir di setiap negara Tahun 2017 sebesar 22,2% (World Health Organization, 2018), Prevalensi balita stunting di Indonesia tahun 2017, prevalensi stunting telah mengalami penurunan menjadi 29,6% (Kemenkes RI, 2018), Lampung berada pada urutan ke-10 sebagai provinsi dengan kategori stunting sangat tinggi (40%) dan kabupaten Lampung Tengah Berdasarkan hasil survei pendahuluan yang penulis lakukan di Desa Tanjung Rejo Kab.Lampung tengah diperoleh data balita stunting berjumlah 40 balita (16,2%),Tujuan penelitian adalah untuk mengetahui Determinan Gagal Tumbuh (Sunting) Pada Anak di Desa Tanjung Rejo Kabupaten Lampung Tengah Tahun 2021. Jenis penelitian kuantitatif dengan menggunakan pendekatan Case control, Besarnya sampel dapat ditentukan dengan rumus Lemeshow, maka jumlah sampelnya 40 Balita untuk kelompok kasus dan 40 balita untuk kelompok Teknik sampling secara simpel random sampling, Analisa Bivariat menggunakan uji Chi Square. dan Analisis Multivariat dengan Uji Regeresi Logistik, Hasil penelitian dikeperoleh hasil p-value 0,000  berarti ada pengaruh Panjang badan lahir dengan Kejadian Stunting.p -value 0,210 dengan OR 0,444 (95% CI 0,122-1.617)   bahwa bahwa berat badan lahir ada hubungan dengan Kejadian Stunting, p-value 0,000  ada pengaruh Pemberian Asi Eksklusif dengan Kejadian Stunting. p-value 0,000  ada pengaruh Pemberian Asi sampai 2 tahun dengan Kejadian Stunting, p-value 0,001  ada pengaruh Status Imunisasi dengan Kejadian Stunting, p-value 0,001  ada pengaruh antara jarak kelahiran dengan Kejadian Stunting, p-value 0,001  ada pengaruh jumlah anak dengan Kejadian Stunting, p-value 0,000  ada pengaruh status ekonomi dengan Kejadian Stunting dan Faktor dengan besar risiko paling besar terhadap kejadian stunting adalah Ekonomi (95% CI 0.852-70.346), Sebaiknya menjadi perhatian dari segi akses ekonomi dan pemenuhan kebutuhan yang cukup maupun kurang bagi keluarga yang memiliki balita yang nantinya akan berpengaruh terhadap meningkatknya kualitas konsumsi pangan anggota keluarga.